Hubungan Pola Makan dan Stres dengan Terjadinya Kekambuhan Gastritis di Wilayah Kerja Puskesmas Poasia Kota Kendari - Putri Anggraeni; Ari Tjahyadi Rafiuddin; Andi Mauliyana (Program Studi Sarjana Kesehatan Masyarakat Universitas Mandala Waluya, 2022)
The data showed that in 2019 there were 2,273 cases;in 2020, there were 1,209 cases, and in 2021 there were 1,937 cases. This study aimed to determine the relationship between diet and stress and the occurrence of gastritis recurrence in the working area of the poasia public health center, kendari city. This type of research was analytic with a cross-sectional study design. The population of this study was patients with gastritis and non-gastritis sufferers totaling 246 respondents with a sample of 72 respondents by purposive sampling. The analysis used univariate and bivariate analysis and was tested using ch-square and the value of phi. This study’s results indicated a significant relationship between eating patterns (x2count = 23,144; = 0,512) and significant relationship between eating stress (x2count = 23,615; 0,515). It is expected for the community, especially gastritis sufferers, to apply a diet with a regular frequency and reduce excessive stress or manage stress appropriately to avoid gastritis.